(untitled) (International Journal of Engineering and Computer Science, 2013)
Network crimes are the most unpredictable calamity on the cyber world. Unauthorized access, hacking, spreading of viruses, smashing computer networks on very large scale, the brutal weapons like email bombing, logic bombs resulting into the disrupt behavior of computer networks are very few incidences of recent days. Security of information systems against them is the protection of availability, confidentiality and integrity. The relative priority and significance of availability, confidentiality and integrity vary according to the information system. The legislation should address computers and computer material as unique objects and cover all computer-related aspects in the categories of crimes by means of computers and crimes against computers. The Union Government of India has started now to establish special cyber crime units for controlling such crimes.